POST-CHORNOBYL TRENDS IN THE PREVALENCE OF DISEASES AND INCIDENCE OF THE CHILDREN’S POPULATION IN UKRAINE - Volosovets, O.P.; Кривопустов, С.П.; Mozyrskaya, O.V.; Skvarskaya, O.O.; Saltanova, S.D.; Yemets, O.V.; Karulina, Yu.V. (World of Medicine and Biology, 2018)
For thirty years (1987 - 2016), the incidence of children living in areas with radioecological territories has increased from 455.4 to 1471.93 per 1000 children, which is almost 3.2 times. At the same time, among the children of these regions, the prevalence of diseases increased from 786 per 1,000 children in 1987 to 2052.69 in 2016, is 2.6 times. An analysis of the health status of the children population living in areas with radioecological control areas and undergoing constant indirect influence of the consequences of the Chernobyl accident indicates that it is progressively deteriorating, which corresponds to the overall dynamics of the health of the children’s population of the country. In all 9 regions with radioecological monitoring areas there is a high incidence of childhood, which, with the exception of indicators of Rivne, Vinnitsa, Volyn and Sumy regions, prevails with the corresponding high rates of morbidity of the children population living in areas without radioecological control areas. Indicators of infant mortality in the Chernihiv, Zhytomyr, Cherkassy and Rivne regions, where the largest number of radioecological monitoring areas is observed, and the largest number of children who have been affected by the Chernobyl accident, exceeded the national indicator. Over the past 22 years, the difference in incidence among children from regions with radioecological control areas and other oblasts has increased by 80.3%, and compared with the national indicator, the difference has increased by 66.8%. Attention is drawn to the highest increase in morbidity and prevalence of tumors, diseases of the endocrine system, circulatory diseases, diseases of the urinary system, musculoskeletal system, congenital anomalies, deformations and chromosomal abnormalities, ear diseases and apoptosis, respiratory diseases. The rate of growth of morbidity for all classes of diseases of children from regions with territories of radioecological control over the past 22 years was + 42.1%, and was the highest compared to the similar parameters in children from areas without territories of radioecological control, which was + 32.9%, with a nationwide growth rate + 36.09%. There is a very high rate of growth rate of the incidence of newborns in children from areas with radioecological control areas + 169.9%. In children from areas without radioecological control areas it was + 163.2% at the national level + 162.3%.